Climate-water governance: a systematic analysis of the water sector resilience and adaptation to combat climate change in Pakistan - Yasin, Hafiz Qaisar; Breadsell, Jessica; Tahir, Muhammad Naveed (IWA Publishing, 2020)
Climate change and water security have become the most challenging global issues of this era, especially for developing countries like Pakistan. Amid many hindrances, poor governance has been identified as one of the most pressing reasons for ineffective action to tackle multifaceted and integrative climate-water issues in Pakistan. This article, therefore, applied a systematic literature review methodology to examine the current climate-water governance archetype, including key areas, major elements, critical gaps, and potential strategy in Pakistan. This study found that key climate-water governance areas in Pakistan are: river basin and watershed management, agriculture and irrigation management, urban and domestic water issues, floods, droughts and disaster management, groundwater management, and transboundary management. Moreover, it is revealed that the major governance elements are political commitment and leadership, policy formulation and regulation, institutional capacity and coordination, stakeholder engagement, and resource management, technology, and infrastructure development. The article also discusses how Pakistan has not effectively employed most of the identified governance elements to tackle its climate-water problems, lacking mostly in political, policy, institutional, coordination, and infrastructure aspects. In conclusion, a four-dimensional governance strategy, encompassing leadership, policy, institutions, and stakeholders is proposed to improve water sector resilience and adaptation to combat climate change in Pakistan.